Relaxation Effects in Self-Discharge Measurements of Lithium-Ion Batteries. Issue 2 (1st February 2023) - Roth, Thomas; Streck, Luiza; Graule, Andreas; Niehoff, Philipp; Jossen, Andreas
Abstract : In order to determine the quality of newly produced lithium-ion cells, self-discharge measurements are performed after manufacturing during the so-called aging step. The aging step is a time-consuming and cost-intensive process due to relaxation effects disturbing the self-discharge measuremtens. Relaxation effects are mainly attributed to voltage relaxation and anode overhang equalization. In this work, different methods for electrical self-discharge measurement, such as the voltage decay method, the voltage hold method, and the capacity loss method, were investigated using commercial Samsung INR21700–50E cylindrical cells (NCA/silicon-graphite) and non-commercial pouch-cells (NMC622/graphite). Various preconditioning methods allowed a distinction to be made between undisturbed, short-term, and long-term disturbed cells. While short-term disturbances subsided after several hours, long-term disturbances due to anode overhang were found to significantly disturb all electrical self-discharge measurements for several weeks. A theoretical explanation was introduced, describing the lithium inventory change due to anode and coupled side reactions being measured differently by voltage- and capacity-based methods. Experimental results confirmed this notion and showed that voltage-based self-discharge measurements underestimated the anode overhang equalization. A comparison to the initial cell aging data indicated that the self-discharge measurement performed shortly after cell formation was disturbed by the anode overhang equalization.